Effects of backward walking as a modality for low back pain reduction in athletes - Dufek, J.; House, A.; Mangus, B.; Mercer, J.; Melcher, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The therapeutic effectiveness of backward walking for treatment of low back pain (LBP) was examined among athletes experiencing LBP and healthy non-athletes. All participants were pre-tested walking backward, performed 10-15 mins of backward walking three days/week for three weeks and were post-tested. Low back sagittal and coronal plane range of motion, shock attenuation (SA), stride length (SL), stride rate (SR), velocity and LBP were evaluated (a=0.05). All variables were significantly different between groups, excluding SA. Velocity, SL and SR were significantly different pre vs post. Owing to the clinical nature of this study, single-subject analyses were performed and identified unique individual responses to the intervention. Results suggest that backward walking may assist some athletes presenting with LBP.